2013
DOI: 10.1371/journal.pone.0057115
|View full text |Cite
|
Sign up to set email alerts
|

Depression-Like Responses Induced by Daytime Light Deficiency in the Diurnal Grass Rat (Arvicanthis niloticus)

Abstract: Seasonal Affective Disorder (SAD) is one of the most common mood disorders with depressive symptoms recurring in winter when there is less sunlight. The fact that light is the most salient factor entraining circadian rhythms leads to the phase-shifting hypothesis, which suggests that the depressive episodes of SAD are caused by misalignments between the circadian rhythms and the habitual sleep times. However, how changes in environmental lighting conditions lead to the fluctuations in mood is largely unknown. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
75
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(83 citation statements)
references
References 49 publications
6
75
2
Order By: Relevance
“…Another study that tested the behavioral effects of short or long photoperiods in hamsters also demonstrated reversed effects on females and males, however the trends were opposite of those we found in the current study: SP female hamsters showed less previous studies in males of other diurnal rodents [31,35,37,40,43]. Yet, female rodents are demonstrated in some studies to be more active than males in the FST [48,49] and moreover, the sensitivity of male and female behavior in the FST to interventions that induce depression-like behavior in males and to antidepressant drugs is different [48,[50][51][52].…”
Section: Accepted Manuscriptcontrasting
confidence: 91%
See 1 more Smart Citation
“…Another study that tested the behavioral effects of short or long photoperiods in hamsters also demonstrated reversed effects on females and males, however the trends were opposite of those we found in the current study: SP female hamsters showed less previous studies in males of other diurnal rodents [31,35,37,40,43]. Yet, female rodents are demonstrated in some studies to be more active than males in the FST [48,49] and moreover, the sensitivity of male and female behavior in the FST to interventions that induce depression-like behavior in males and to antidepressant drugs is different [48,[50][51][52].…”
Section: Accepted Manuscriptcontrasting
confidence: 91%
“…This work demonstrated that several diurnal rodent species, including the fat sand rat (Psammomys obesus), grass Nile rat (Arvicanthis niloticus), Mongolian gerbils (Meriones unguiculatus) and the degu (Octodon degus) indeed change their behavior and show depressive-and anxiety-like phenotypes in response to changes in day length [14][15][16][17][18]. Moreover, the behavioral changes displayed by these diurnal rodents respond to similar treatment used to alleviate symptoms of SAD in humans including antidepressant drugs, bright light exposure and voluntary exercise [19][20][21][22].…”
Section: Introductionmentioning
confidence: 88%
“…In accordance with this speculation, several studies have indeed established the model of SAD in diurnal rodents [8][9][10][11][12]. These animals showed depression-related symptoms when exposed to 3 weeks or more of short photoperiod.…”
Section: Introductionmentioning
confidence: 63%
“…Although a variety of laboratories have shortened the length of photoperiod to model SAD in rodents [8][9][10][11][12][13][14][15], the effects of short photoperiod on depression-like measures in rodents Fig. 4.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation